1979
DOI: 10.1111/j.1399-0039.1979.tb00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an HLA‐Linked Resistance Gene in Buerger's Disease

Abstract: The incidence of Thromboangiitis Obliterans in brothers and the high prevalence in some ethnic groups have led us to investigate the histocompatibility HLA—A, B and DR antigens of 46 Buerger's disease patients. The main result indicates a marked decreased frequency of the B12 antigen: 2.2% vs 28% in controls. Our study suggests that Buerger's disease is, on the basis of HLA antigens, a distinct immunogenetic entity and not a particular form of arteriosclerosis. Moreover, this disorder may represent a clue to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Patients with Buerger's disease present a statistically significantly higher frequency of HLA‐DR4 and a significantly lower frequency of the HLA‐DRW6 antigen. This observation may serve as further evidence that an autoimmune mechanism is involved in TAO [22,24]. Our study complements these findings, further emphasizing the participation of autoimmune mechanisms in the aetiology of the development of TAO, as we show significant increases of IL‐17 and IL‐23, cytokines related closely to autoimmunity activation [25–27].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Patients with Buerger's disease present a statistically significantly higher frequency of HLA‐DR4 and a significantly lower frequency of the HLA‐DRW6 antigen. This observation may serve as further evidence that an autoimmune mechanism is involved in TAO [22,24]. Our study complements these findings, further emphasizing the participation of autoimmune mechanisms in the aetiology of the development of TAO, as we show significant increases of IL‐17 and IL‐23, cytokines related closely to autoimmunity activation [25–27].…”
Section: Discussionsupporting
confidence: 86%
“…By using an antigen-sensitive thymidine-incorporation assay, Adar et al [21] showed that patients with TAO have an increased cellular sensitivity to types I and III collagen compared to patients with arteriosclerosis obliterans or healthy males. De Moerloose et al [22] found a marked decrease in the Similarly to other autoimmune diseases, TAO may have a genetic predisposition without a direct 'causative' gene mutation. Most investigators believe that TAO is an immunemediated endarteritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in several human leukocyte antigen (HLA) subtypes has been reported in patients with Buerger's disease by several investigators: A9, B5, A1, B8 and DR4 [19,20]. It has also been suggested that HLA-B12 antigen may be associated with disease resistance, since it is almost never detected in patients with Buerger's disease [21]. Eichhorn et al [22] identified significantly elevated antiendothelial cell antibodies in a small group of patients with active Buerger's disease [23].…”
Section: Discussionmentioning
confidence: 96%
“…70-72 There is a negative association between this disease and HLA-B12. 73 The incidence of Buerger disease is low among individuals with HLA-DPB1*0401 and those with HLA-DRB*1302. 74 …”
Section: Pathogenesismentioning
confidence: 99%